Epidemiological Trends of Acute Chemical Poisoning among Children over a Recent Three-Year Period in Saudi Arabia - Mohammed Merae Alshahrani; Hussein Ayed Albogami; Ali Ahmad Asiri; Khaled Saad Al haydhah; Ibrahim Mohammed Aldeailej; Mohammed Abdullah Aldehaim; Mahmoud Yousef Lubbad; Lolwah Abdulaziz Alalyan; Abdullah Fayez Alasmari; Ismail Yahya Al salem; Abdulaziz Alqahtani; Ahmed Abdullah Al Awadh (MDPI AG, 2023)
Acute intoxication from chemicals is a major medical emergency that can result in illness and mortality. This retrospective study aims to evaluate acute chemical poisoning incidents among children in Saudi Arabia from 2019 to 2021. A total of 3009 children were recorded as being chemically intoxicated. The SPSS/PC statistics package was used for the statistical analysis. The acute chemical poisoning incidents that occurred in the age groups were <1 year: 237 (7.8%), 1-5 years: 2301 (76.4%), 6-12 years: 214 (7.1%), and 13-19 years: 257 (8.5%). The mean rate of acute chemical poisoning in the northern region was 40.1%. The most common poisonous agents were organic solvents (20.4%) and disinfection agents (22.7%). Interestingly, there is a significant relationship between the different types of acute chemical poisoning and various factors, including gender, age, the location where acute chemical intoxication occurred, the type of exposure, and whether these were intentional or unintentional events. The data suggest that the northern region of Saudi Arabia has had the highest number of recorded incidents of acute chemical poisoning over the last three years (2019-2021). Individuals between 1-5 years old were the worst hit. Organic solvents and detergents were to blame for the acute unintentional chemical poisonings that took place in homes. Therefore, educating the public about chemical poisoning and reducing children's exposure to toxic chemicals requires educational programs, which may help to reduce chemical poisoning occurrence.